Aukus (Australia-united kingdom-united states) threat to Indo-pacific security - Ismiyatun Ismiyatun; Ita Puji Lestari (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The Indo-Pacific region, as the fastest-growing and economically significant area in the world, is increasingly becoming a focal point of geopolitical tensions, particularly with the emergence of the AUKUS alliance. The introduction of nuclear-powered submarines by Australia under AUKUS presents a profound threat to the stability and security of the Indo-Pacific, challenging existing treaties like the Southeast Asia Nuclear Weapon Free Zone (SEANWFZ) and potentially igniting an arms race. Understanding these dynamics is critical for shaping policies that can mitigate the risks of escalating military conflicts and ensure regional stability. The primary objective of this study is to critically analyze the security implications of the AUKUS alliance on the Indo-Pacific region, with a particular focus on how the introduction of nuclear-powered submarines by Australia could undermine regional treaties and provoke an arms race. This study employs a qualitative research approach, specifically using the method of a literature review. The data sources for this study consist of secondary data, including academic journal articles, books, governmental and non-governmental reports, and policy briefs. Data collection was conducted by systematically searching for relevant literature using keywords such as "AUKUS," "Indo-Pacific security," "military alliances," and "geopolitical threats." The literature was then reviewed and categorized based on its thematic relevance to the study. For data analysis, a thematic analysis method was used to identify and interpret patterns within the literature. The research results show: the impact of defense spending in the Indo-Pacific can be influenced by changes in regional dynamics caused by the AUKUS agreement. Countries can change their defense budgets based on their assessment of security threats in the region and changes in the balance of power. Countries can provide funding to enhance their cybersecurity capabilities, which could include investing in cyber defense measures to protect critical military infrastructure and networks. Investments in capital and technology and equipment are part of defense expenditure. CAUCUS can enhance economic cooperation and integration between participating countries and open new opportunities for trade, investment, and technology transfer in the Indo-Pacific region. This could impact the economic landscape resulting from defense partnerships.